Investigating the nature of active forces in tissues reveals how contractile cells can form extensile monolayers - Balasubramaniam, L; Doostmohammadi, A; Saw, TB; Narayana, GHNS; Mueller, R; Dang, T; Thomas, M; Gupta, S; Sonam, S; Yap, AS; Toyama, Y; Mège, R-M; et al. (Nature Research, 2021)
Actomyosin machinery endows cells with contractility at a single-cell level. However, within a monolayer, cells can be contractile or extensile based on the direction of pushing or pulling forces exerted by their neighbours or on the substrate. It has been shown that a monolayer of fibroblasts behaves as a contractile system while epithelial or neural progentior monolayers behave as an extensile system. Through a combination of cell culture experiments and in silico modelling, we reveal the mechanism behind this switch in extensile to contractile as the weakening of intercellular contacts. This switch promotes the build-up of tension at the cell–substrate interface through an increase in actin stress fibres and traction forces. This is accompanied by mechanotransductive changes in vinculin and YAP activation. We further show that contractile and extensile differences in cell activity sort cells in mixtures, uncovering a generic mechanism for pattern formation during cell competition, and morphogenesis.